The essence of surviving COVID-19: A phenomenology Study - Idauli Simbolon (JKP (Jurnal Keperawatan Padjajaran), 2022)
Background: COVID-19 is a respiratory infection that has claimed the lives of many people. It caused many changes in society; it impacted physically, emotionally, and most of all socially. The impact can be light or severe, depending on the severity of the diseases and the individual ability to cope with the disease. Although many died from this disease, many also survived.